Tumour necrosis factor-α polymorphism as one of the complex inherited factors in pemphigus - Jolanta Dorota Torzecka; Joanna Narbutt; Anna Sysa-jedrzejowska; Maciej Borowiec; Anetta Ptasinska; Grzegorz Woszczek; Marek L. Kowalski (Mediators of Inflammation)
The aim of our study was to analyse a significance of tumour necrosis factor (TNF)-α promoter gene polymorphisms in relation to the HLA-DR locus in genetic predisposition to pemphigus. TNF-α gene polymorphisms in position -238 and -308 were identified using a modified polymerase chain reaction-restriction fragment length polymorphism method in 53 patients with pemphigus (38 with pemphigus vulgaris, 15 with pemphigus foliaceus) and 87 healthy controls. The HLA-DRB1 locus was typed using the polymerase chain reaction SSO method in all the patients and 152 population controls.